Functionalized PEG-oligo(L-lysine)-PCL micelle system for the delivery of bioactive agents based on pH-sensitive degradation. (19th October 2020) - Kang, Jungkyu; Jeon, Seong Ik; Chung, In Jae; Ahn, Cheol-Hee
Abstract: Methoxy poly(ethylene glycol) amine with a molecular weight of 5 K and ϵ-caprolactone with a molecular weight of 3 K were conjugated to five lysine residues with molecular weight and M w / M n of 9.6 K and 1.04, respectively. The shift of peak molecular weight and narrow molecular weight distribution in a gel permeation chromatography (GPC) trace without any noticeable shoulder as well as 1 H nuclear magnetic resonance analysis confirmed the successful synthesis of the copolymer. Polymeric micelles, of size around 60 nm, were formed by dialysis and crosslinked micelles (CMs) were prepared by adding a crosslinker, terephthalaldehyde, to generate weak acid-labile benzoic-imine bonds in the interface of the micelle-forming amphiphilic copolymer. The critical micelle concentrations of non-crosslinked micelles and CMs were determined to be 4.26 × 10 –2 mg ml −1 and 7.01 × 10 –3 mg ml −1, respectively. The hydrolysis rate of the CMs is highly pH-dependent and much more rapid at mild acid than physiological conditions. Doxorubicin was successfully loaded into the CMs and a controlled pH-dependent release behavior was observed. The enhanced micelle stability opens a way for preparing long-circulating delivery systems encapsulating poorly water-soluble drugs.